Development of E-Modules Based On The Contextual Teaching and Learning (Ctl) Approach Using Geogebra for The Topics of Triangles and Quadrilaterals - Juliani Putri, Vera; Noviarni, Noviarni (Universitas PGRI Semarang, 2026)
This study aims to develop an e-module based on the Contextual Teaching and Learning (CTL) approach, supported by GeoGebra, on the topics of triangles and quadrilaterals, and to determine its validity, practicality, and effectiveness in terms of student learning outcomes. The research design employed is Research and Development (RD) using the ASSURE development model. The research subjects were seventh-grade students at State Junior High School 2 Pekanbaru during the 2025/2026 academic year. Research instruments included validation sheets for subject matter experts and educational technology experts, a student response questionnaire, and a learning outcome test. The results of the subject matter expert validation yielded a percentage of 83.86%, and the educational technology expert validation yielded 87.58%; both fall into the “highly valid” category. The results of the practicality test on the small group yielded a percentage of 88.23%, and on the limited group, 88.75%; both fall into the “highly practical” category. Based on the data analysis results, the calculated t-value (8.2566) was greater than the critical t-value (1.6698) at a 5% significance level, with the average learning outcome of the experimental class (79.04) being higher than that of the control class (51.69), indicating a significant difference in learning outcomes. Thus, the CTL-based e-module supported by GeoGebra on the topics of triangles and quadrilaterals is deemed valid, practical, and effective for improving student learning outcomes, and can serve as an innovative teaching material alternative in mathematics education at the secondary school level.